Dynamic changes in carbohydrate components and the bacterial community during the ensiling of wilted and unwilted sweet sorghum - Sun, Zhiqiang; Liu, Yiting; Ji, Fangcai; Li, Shuangye; Wang, Lei; Zhou, Zhenming; Wu, Zhe; Yu, Zhu (Frontiers in Microbiology, 2024)
Sweet sorghum can be used to produce a substantial quantity of biofuel due to its high biological yield and high carbohydrate content. In this study, we investigated the dynamic changes in fermentation characteristics, carbohydrate components, and the bacterial community during the ensiling of wilted and unwilted sweet sorghum. The results revealed a rapid fermentation pattern and high-quality fermentation quality in wilted and unwilted sweet sorghum, wherein lactic acid, and acetic acid accumulated and stabilized during the initial 9 days of ensiling, with the pH values less than 4.2, until 60 days of ensiling. We found that the ensiling of sweet sorghum involved the degradation (5%~10%) of neutral detergent fiber (NDF) and hemicellulose and that the degradation of NDF fit a first-order exponential decay model. A shift in dominance from Lactococcus to Lactobacillus occurred before the first 9 days of ensiling, and the abundance of Lactobacillus (r=-0.68, P<0.001) was negatively correlated with the NDF content. The relative abundances of Lactobacillus in wilted and unwilted sweet sorghum after ensiling for 60 days were 76.30% and 93.49%, respectively, and relatively high fermentation quality was obtained. In summary, ensiling is proposed as a biological pretreatment for sweet sorghum for subsequent biofuel production, and unlike other materials, sweet sorghum quickly achieves good fermentation quality and has great potential for bioresource production.